2013
DOI: 10.1159/000347051
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between Experimental Dental Pellicles and Stannous-Containing Toothpaste on Dental Erosion-Abrasion

Abstract: The interaction between stannous-containing dentifrice slurry and experimentally formed pellicles was investigated on enamel and root dentin using an erosion-remineralization-abrasion cycling model. The remineralizing solutions contained no proteins (negative control), mucin, casein, mucin + casein or albumin, for experimental pellicle formation. Toothbrushing was performed with fluoride toothpaste, with (TP + Sn) and without (TP) 3,500 ppm Sn. TP + Sn reduced surface loss for both enamel and root dentin (p < … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
1
9

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 51 publications
1
21
1
9
Order By: Relevance
“…Thus, the present study included a series of experiments that tested the effects of 3 different formulations and a placebo under changing erosive conditions using 1 type of acid. Citric acid was used because it is often the demineralisation agent in erosion or erosion/abrasion studies; ranges of concentrations and pH values were chosen according to the literature (for example Lagerweij et al [2006]; Attin et al [2007]; Hara et al [2009]; Ganss et al [2012]; Hara et al [2013]). The other parameters (erosion time, brushing time, brushing force and remineralisation procedure) were kept constant and followed our previous experiments [Ganss et al, , 2012 as well as recommendations for erosion and erosion/abrasion studies [Wiegand and Attin, 2011;Shellis et al, 2011].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the present study included a series of experiments that tested the effects of 3 different formulations and a placebo under changing erosive conditions using 1 type of acid. Citric acid was used because it is often the demineralisation agent in erosion or erosion/abrasion studies; ranges of concentrations and pH values were chosen according to the literature (for example Lagerweij et al [2006]; Attin et al [2007]; Hara et al [2009]; Ganss et al [2012]; Hara et al [2013]). The other parameters (erosion time, brushing time, brushing force and remineralisation procedure) were kept constant and followed our previous experiments [Ganss et al, , 2012 as well as recommendations for erosion and erosion/abrasion studies [Wiegand and Attin, 2011;Shellis et al, 2011].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the tin fluoride, one study showed that natural pellicle formed in situ did not result in any negative influence on its protective effect [Hove et al, 2008]. Also, when the pellicle was simulated in an in vitro study significantly less erosive wear for Sn-containing toothpastes was observed [Hara et al, 2013]. Regarding the CO 2 laser irradiation, it is also probable that it would not negatively influence the effects, since pellicles have a high protein content (proteins, peptides, lipids, and other macromolecules) and these components show a very poor absorption at 10.6 μm, being almost transparent Zuerlein et al, 1999].…”
Section: Discussionmentioning
confidence: 99%
“…titanium tetrafluoride or stannous fluoride, were shown to be of higher efficacy. 3,4 In the last years, numerous toothpastes with "anti-erosive" or "repairing" claims were marketed, which contain other active ingredients besides fluorides, e.g. hydroxyapatite nanoparticles, zinc-carbonate-hydroxyapatite nanoparticles, potassium nitrate, stannous salts, chitosan and/or proteins.…”
Section: Introductionmentioning
confidence: 99%